The Poles in America, 1608-1972; a chronology & fact book. - Renkiewicz, Frank, 1935- (Ethnic chronology series, 1973)
Chronologically traces the history and accomplishments of Poles in the United States from 1608-1972. Includes reproductions of documents pertinent to Polish-American history.